Realizace zastřešení bytového domu v obci Pístov - Kratochvíl, Tomáš (Vysoké učení technické v Brně. Fakulta stavební, 2016)
Tato práce se zabývá problematikou jednoplášťových plochých střech a konkrétním provedením realizace zastřešení bytového domu. Cílem je dosažení té nejlepší varianty z hlediska finančního, časového nebo technologického řešení výstavby ploché střechy bytového domu v obci Pístov.

This work deals with the warm flat roofs and the particular embodiment of the cover residential building the flat roofs. The aim is to achieve the best options in terms of finance, time or technological solutions to the construction of the flat roof of a residential building in the village Pístov
Realization of roofing of a residential building in the village Pístov
Keywords: Plochá střecha; jednoplášťová plochá střecha; zastřešení; spádová vrstva; tepelná izolace; polystyren; asfaltové pásy; asfaltový modifikovaný pás; atika; střešní vtok; separační vrstva; kamenivo; beton; Flat roof; warm flat roof; roofing; screed to fall; thermal insulation; expanded polystyrene; asphalt sheet; modifed bitumen membrane; parapet wall; roof drain; separation layer; aggregate; concrete